Sistem Pendaftaran Siswa Baru Untuk Mengklasifikasikan Kelas Di Mts Darussalam Jombang - Wienda Gatoet Purwandono; Tjatursari Widiartin; Noven Indra Prasetya (Melek IT : Information Technology Journal, 2017)
New student registration system to classify class is used to facilitate the prospective students from outside the town of jombang in the registers without coming directly to the school to sign up. In addition, this application can also help teachers in making the Division of class or classification test scores without experiencing the confusion in the Division and studying will become more effective. The method used i.e. the method waterfall, waterfall method is having 5 stages and in applying it in penalties the problem identification, analysis systems, system design and test implements and maintenance or evaluation. The results shown are a form of information systems and applications, the user can know the results and the results of the registration division of class or classification class in addition users can also find out other information.